A method for the assessment of the coefficient of friction of articular cartilage and a replacement biomaterial. (March 2020) - Mahmood, Humaira; Eckold, David; Stead, Iestyn; Shepherd, Duncan E.T.; Espino, Daniel M.; Dearn, Karl D.
Abstract: Replacement biomaterials for articular cartilage should encourage a coefficient of friction similar to the natural joint. Whilst the literature has assessed the coefficient of friction of articular cartilage against that of a potential biomaterial, it is unknown what the friction of articular cartilage in sliding against a surface defect, repaired with a biomaterial is. This evaluation is crucial to allow for the development of effective biomaterials to closely have the behaviour of articular cartilage. Thus, the aim of this study was to develop a novel technique for the assessment of the coefficient of friction of replacement biomaterials within articular cartilage, with this original testing configuration. For this study, a biomaterial was induced within an artificial defect perforated on the surface of bovine articular cartilage, whilst the material was assessed in sliding against articular cartilage itself. Calcium alginate was selected as the sample biomaterial for evaluation in this study. The tests were performed in sliding on a pin-on-disc tribometer in Ringer's solution. Two further tests were carried out, one as a benchmark comparison of a cartilage pin against a cartilage plate, as well as a cartilage pin against an aluminium plate. A constant induced stress of 0.06 MPa was applied at a frequency of 1 Hz. For the cartilage-cartilage, cartilage/hydrogel-cartilage and cartilage-aluminium test, the overall median coefficient of friction extracted across six repeats was of 0.36, 0.38 and 0.32, respectively. Statistical insignificance was identified across all three groups tested ( p > 0.05). Similarity was observed in the coefficient of friction of cartilage-cartilage and cartilage/hydrogel-cartilage tests, however high-speed data identified the greatest wear for the cartilage/hydrogel-cartilage test. Highlights: This study develops a method for the evaluation of the coefficient of friction for cartilage replacement biomaterials. The cartilage/hydrogel-cartilage test adopts a similar coefficient of friction to the cartilage-cartilage test. Statistical insignificance exists between cartilage-cartilage, cartilage/hydrogel-cartilage and cartilage-aluminium; p > 0.05. High-speed data identifies the largest energy dispersion for cartilage/hydrogel-cartilage, therefore implying greatest wear.